Joint disease-specificity at the regulatory base-pair level - Pushpanathan Muthuirulan (Nature Portfolio, 2021)
While many genetic loci have been found to be associated with disease, not many have had their causal variants and mechanisms investigated. Here, the authors experimentally dissect two loci near GDF5 which are associated with two different joint disorders and which map to independent regulatory elements.